(untitled) (Bangladesh Critical Care Journal, 2022)
Traumatic brain injury (TBI) can be defined as the disruption in brain function, or other evidence of brain pathology, caused by an external physical force. Management of TBI depends on, if the injury is focal or diffuse. Focal can be epidural or intra cerebral and diffuse lesions can present as multiple contusions/DAI. A basic understanding of anatomy of central nervous system and some working knowledge of physiology of brain help in management of TBI. According to severity there are three types of TBI patients. They are: mild (GCS 13-15), moderate (GCS 9-12) and severe (GCS 3-8). TBI may be primary or secondary. Primary injuries include contusion, hematoma, subarachnoid hemorrhage, diffuse axonal injury etc. Secondary injuries can manifest as cerebral oedema, raised intra cranial pressure etc. Airway management and cervical spine immobilization are important early steps in management. Hypoxia and hypercarbia must be avoided and attention is always paid to ventilation status of patients. Mean arterial pressure (MAP) should be monitored and maintained at 80-90 mm of Hg. Intracranial pressure (ICP) should be checked whenever feasible and monitored so raised ICP can be controlled. Adequate pain control and sedation, using mannitol, hypertonic saline should be used as needed to control raised ICP. Invasive ICP monitoring and cerebrospinal fluid diversion should be used in patient who decompensate and decision to do decompressive craniectomy is often made by neurosurgeons. Body temperature in TBI patients should be maintained under 37o C. Neurologic conditions like brainstem dysfunction, intracranial hypertension, altered level of consciousness etc. and respiratory conditions like ARDS, hypoxaemia , neurogenic pulmonary oedema etc. warrants endotracheal intubation and mechanical ventilation. TBI patients requiring haemo dialysis usually need special modification in protocol to avoid pulmonary oedema and fluctuation in blood pressure. Monitoring TBI patients is done by routine assessment of GCS, pupillary size and reaction, motor responses. ICP monitoring is to be done if feasible. By aggressive monitoring secondary brain injuries can be avoided or managed. Outcome of management of TBI patients in ICU depends on severity of primary and secondary injuries of brain, status of GCS on presentation, advanced age (>65yrs), presence or absence of co morbidities and severity of associated injuries. Bangladesh Crit Care J September 2022; 10(2): 135-141